CONFLICT MANAGEMENT STRATEGY IN PRINCIPAL LEADERSHIP FROM AN ISLAMIC PERSPECTIVE - Rahmatullah; M. Ilyas; Azmir Suljic; Mutamakin (STAI Ma'had Aly Al-Hikam Malang, 2024)
Conflict is one of the problems faced by many organizations, especially non-profit organizations such as educational institutions (schools). School leaders or principals play an important role in managing conflict in order to achieve the vision, mission and goals of the organization. This article aims to describe first, the nature, activities and management of conflict. Second, the nature and role of school principal leadership. Third, conflict management strategies in the leadership of school principals from an Islamic perspective. The research method used is literature study, researchers collect data from various sources, reduce and analyze, and draw conclusions. The research results show that: first, the essence of conflict is differences of opinion, while conflict activities are related to competition, conflict management is carried out through introspection, evaluation, identification, and knowing options. Second, the essence of leadership is influencing, while the principal's leadership role includes as a formal official, manager, leader, supervisor, administrator, educator, and as staff. Third, conflict management strategies in Islamic perspective principal leadership are leadership perspectives and behavior. Keywords: Conflict Management; Leadership; School. ABSTRAK Konflik adalah salah satu masalah yang dihadapi banyak organisasi khususnya organisasi non-profit seperti lembaga pendidikan (sekolah). Pemimpin atau kepala sekolah berperan penting dalam mengelola konflik agar dapat mencapai visi, misi, dan tujuan organisasi. Artikel ini bertujuan untuk mendiskripsikan tentang pertama, hakikat, aktivitas dan pengelolaan konflik. Kedua, hakikat dan peran kepemimpinan kepala sekolah. Ketiga, strategi pengelolaan konflik dalam kepemimpinan kepala sekolah perspektif Islam. Metode penelitian yang digunakan adalah studi literatur, peneliti melakukan pengumpulan data dari berbagai sumber, mereduksi, dan menganalisis, serta mengambil kesimpulan. Hasil penelitian menunjukkan bahwa pertama, hakikat konflik adalah perbedaan pendapat, sedangkan aktivitas konflik berkenaan dengan kompetisi, pengelolaan konflik dilakukan dengan Introspeksi, evaluasi, identifikasi, dan mengetahui pilihan. Kedua, hakikat kepemimpinan adalah mempengaruhi sedangkan peran kepemimpinan kepala sekolah diantaranya sebagai pejabat formal, manajer, pemimpin, supervisor, administrator, pendidik, dan sebagai staff. Ketiga, strategi pengelolaan konflik dalam kepemimpinan kepala sekolah perspektif Islam diantaranya meliputi cara pandang dan perilaku kepemimpinan. Kata kunci: Pengelolaan Konflik; Kepemimpinan; Sekolah.